An introduction to Black studies - Jackson, Eric, 1965- (The University Press of Kentucky, 2023)
"For hundreds of years, the American public education system has neglected to fully examine, discuss, and acknowledge the vast and rich history of people of African descent who have played a pivotal role in the transformation of the United States. The establishment of Black studies departments and programs represented a major victory for higher education and a vindication of Black scholars such as W. E. B. Du Bois and Nathan Huggins. This emerging field of study sought to address omissions from numerous disciplines and correct the myriad distortions, stereotypes, and myths about persons of African descent. In An Introduction to Black Studies, Eric R. Jackson demonstrates the continuing need for Black studies, also known as African American studies, in university curricula. Jackson connects the growth and impact of Black studies to the broader context of social justice movements, emphasizing the historical and contemporary demand for the discipline. This book features seventeen chapters that focus on the primary eight disciplines of Black studies: history, sociology, psychology, religion, feminism, education, political science, and the arts. Each chapter includes a biographical vignette of an important figure in African American history, such as Frederick Douglass, Louis Armstrong, and Madam C. J. Walker, as well as student learning objectives that provide a starting point for educators. This valuable work speaks to the strength and rigor of scholarship on Blacks and African Americans, its importance to the formal educational process, and its relevance to the United States and the world"--